Two Blind Individuals in a Forest: Implementing Project-Based Learning in Nutrition and Food Technology in Secondary Schools in Kampala, Uganda - Kansiime, E; Esaete, J; Tumuhimbise, A (African Journal of Education and Practice, 2024)
Purpose: In this study, we explored how project-based learning is used in Nutrition and Food Technology in Uganda. Methodology: Using a mixed methods research approach, 12 focus group discussions were conducted with student project group leaders and considered nine for analysis (n = 50) 12 key informant interviews were done with NFT teachers and considered six for analysis because saturation point was reached. Also, quantitative data was collected from 197 learners who were not group leaders using questionnaires. Findings: The study revealed that the majority of projects in the NFT syllabus were only on food processing with none on topics that link nutrition to health. It further revealed that PBL was used as an additional practice for material taught initially by other means (Mean = 2.72; SD = 0.58), with limited writing of proposals (Mean = 1.47; SD = 0.85) with a narrow focus on 21st-century skills. Also, PBL strongly focused on the originality of the products (Mean = 2.53; SD = 0.82) with overall, an overemphasis on projects for assessment instead of learning. Unique Contribution to Theory, Practice and Policy: Nutrition and Food Technology (NFT) teachers should use PBL as the central teaching method. The National Curriculum Development Centre's guidance that projects should be done after a topic has been taught should be reviewed. Also, the National Curriculum Development Centre should explore the possibility of reviewing the current NFT syllabus to include projects on nutrition and health.